Carbon pool assessment in Gmelina arborea under agroforestry system at Jabalpur district of Madhya Pradesh - BERRY, NANITA; Rai, Nikita; Shukla, Akash (Indian Journal of Agroforestry, 2023)
Climate change, land degradation, poor crop production due to the unexpected climate issues like heavy, erratic rainfall and drought is frequently faced by farmers in all over the country since past three - four years. To minimize this impact, an experiment was laid out at Tropical Forest Research Institute, Jabalpur India, in 2017-2021 to assess the carbon stock in existing 5 year old Gmelina arborea plantation spaced at 5m x 5m intercropped with different shade loving crops like Curcuma longa, Zingiber officinale, Piper betle and Asparagus racemosus. Carbon stock and Carbon sequestration was assessed by non destructive method for 4 consecutive years i.e. 6th, 7th, 8th and 9th year old G. arborea. Results revealed that maximum carbon stock i.e. 4.59, 10.35, 13.26 and 19.40 t ha-1 was recorded under Treatment-1 (G. arborea + C. longa + Z. officinale + P. betle ) , while minimum Carbon stock i.e. 0.67 and 2.07 t ha-1 during 6th and 7th year and 3.58 and 4.57 t ha-1 under Treatment-6 (Sole G. arborea) during 8th to 9th year. Also calculated Carbon sequestration maximum (16.80, 37.88, 48.53 and 70.99 t ha-1) under T-1 while minimum in T-4 i.e. 2.45 and 7.58 t ha-1 in 6th and 7th year respectively, in the 8th and 9th year Treatment-6 (Sole G. arborea) showed minimum Carbon sequestration with 13.10 t ha-1 and 16.73 t ha-1 respectively. Based on regression analysis, linear increase in carbon stock was estimated with basal area, volume and above ground biomass, increase in carbon stock (t ha-1) could be predicted by 1.887, 0.447 and 0.5 t ha-1 respectively with the increase of one unit of each parameters. Present study suggested that G. arborea based agroforestry system has potential to improve the micro climate by absorbing the atmospheric carbon besides generating additional income to the farmers.